Ответ:3*1 2/3-2= 3*5/3-2=5-3=2
Пошаговое объяснение:
Ответ:
Пошаговое объяснение:
х длина прямоугольника
у см ширина прямоугольника
Отсюда следует
2(х+у) = 26 => х+у = 13 => х = 13 - у
ху = 42 (Вместо X ставим х = 13 - у) у(13-у) = 42
у(13-у) = 42
13у - у² = 42
у² - 13у + 42 = 0 (считаем квадратное уравнение)
Д = 169 - 168 = 1
у1 = (13 -1)/2 = 6
у2 = (13 + 1) /2 = 7
при у = 6 см, х = 13-6 = 7 см
при у = 7 см, х = 13-7 = 6 см.
Ответ: 6 и 7 см.
(5a-10-3a+8)(5a-10+3a-8)+132=(2a-2)(8a-18)+132a=16a^2 -16a-36a+36+132a=
16a^2+80a+36;
16 * (-6)^2 +80*(-6) +36 = 576 -480 +36 =132
5+3(2у-7)= 5+6у-21=6у-16
если у=-18, то 6у-16=6*(-18)-16=-124